Beispiel Nr: 08
$ \text{Gegeben:}\\\text{Breite} \qquad b \qquad [m] \\ \text{Umfang} \qquad U \qquad [m] \\ \\ \text{Gesucht:} \\\text{Länge} \qquad a \qquad [m] \\ \\ a = \frac{U - 2\cdot b}{ 2}\\ \textbf{Gegeben:} \\ b=8m \qquad U=48m \qquad \\ \\ \textbf{Rechnung:} \\ a = \frac{U - 2\cdot b}{ 2} \\ b=8m\\ U=48m\\ a = \frac{48m - 2\cdot 8m}{ 2}\\\\a=16m \\\\\\ \tiny \begin{array}{|l|} \hline b=\\ \hline 8 m \\ \hline 80 dm \\ \hline 800 cm \\ \hline 8\cdot 10^{3} mm \\ \hline 8\cdot 10^{6} \mu m \\ \hline 0,008 km \\ \hline \end{array} \tiny \begin{array}{|l|} \hline U=\\ \hline 48 m \\ \hline 480 dm \\ \hline 4,8\cdot 10^{3} cm \\ \hline 4,8\cdot 10^{4} mm \\ \hline 4,8\cdot 10^{7} \mu m \\ \hline 0,048 km \\ \hline \end{array} \tiny \begin{array}{|l|} \hline a=\\ \hline 16 m \\ \hline 160 dm \\ \hline 1,6\cdot 10^{3} cm \\ \hline 1,6\cdot 10^{4} mm \\ \hline 1,6\cdot 10^{7} \mu m \\ \hline 0,016 km \\ \hline \end{array}$